Pyridine-2-carboxylic acid as an effectual catalyst for rapid multi-component synthesis of pyrazolo[3, 4-b]quinolinones. Issue 58 (25th September 2020) - Sharma, Mayank G.; Vala, Ruturajsinh M.; Patel, Hitendra M.
Abstract : Green synthesis of pyrazolo[3, 4- b ]quinolinones was designed using bioproduct pyridine-2-carboxylic acid (P2CA) as a green and efficient catalyst. Abstract : Green synthesis of pyrazolo[3, 4- b ]quinolinones was designed using bioproduct pyridine-2-carboxylic acid (P2CA) as a green and efficient catalyst. The multi-component reaction of aldehydes, 1, 3-cyclodiones and 5-amino-1-phenyl-pyrazoles regioselectively produced pyrazolo[3, 4- b ]quinolinones in excellent yield (84–98%). Recyclization of the catalyst was also investigated. The electronic effect of the various substituents in aromatic rings indicated that the reaction proceeded through the carbocation intermediate. This newly designed protocol very quickly constructed products conventionally under milder conditions.